A new achromatic glass for near infrared laser instruments - Al-Hamdani, Ali H. (Iraqi Journal of Laser, 2009)
This research investigates new glasses which are best suitable for design of optical systems working in the infrared region between 1.01 to 2.3μm. This work is extended to Oliva & Gennari (1995,1998) research in which they found that the best known achromatic pairs are (BAF2-IRG2; SRF2- IRG3; BAF2-IRG7; CAF2-IRGN6; BAF2-SF56A and BAF2-SF6). Schott will most probably stop the production of these very little used and commercially uninteresting IRG glasses. In this work equally good performances can be obtained by coupling BAF2, SRF2&CAF2 with standard glasses from Schott or Ohara Company. The best new achromatic pairs found are (SRF2-S-TIH10; CAF2-S-LAL9; CAF2-SLAL13 and CAF2-S-BAH27). These new achromatic pairs are analyzed by using ZEMAX ray tracing program to design and analyze the same F/2 camera used by Oliva and for the same near infrared region (1.01-2.3μm). The results show that these pairs of glass have good performance in infrared design applications.